2018
DOI: 10.7717/peerj.4452
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of shifts of koala (Phascolarctos cinereus) intestinal microbial communities associated with antibiotic treatment

Abstract: Koalas (Phascolarctos cinereus) are arboreal marsupials native to Australia that eat a specialized diet of almost exclusively eucalyptus leaves. Microbes in koala intestines are known to break down otherwise toxic compounds, such as tannins, in eucalyptus leaves. Infections by Chlamydia, obligate intracellular bacterial pathogens, are highly prevalent in koala populations. If animals with Chlamydia infections are received by wildlife hospitals, a range of antibiotics can be used to treat them. However, previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 45 publications
(53 reference statements)
0
33
0
Order By: Relevance
“…Approximately 200 mg of the pellet from the homogenized skin smears and gut contents was put into a 1·5‐ml Eppendorf tube for DNA extraction (Dahlhausen et al . ). The total DNA from the fish samples was extracted using a DNeasy Blood and Tissue Kit (Qiagen, Crawley, UK) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 97%
“…Approximately 200 mg of the pellet from the homogenized skin smears and gut contents was put into a 1·5‐ml Eppendorf tube for DNA extraction (Dahlhausen et al . ). The total DNA from the fish samples was extracted using a DNeasy Blood and Tissue Kit (Qiagen, Crawley, UK) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 97%
“…For example, Chlamydia infections are highly prevalent in captive koalas (Phascolarctos cinereus), which are treated with antibiotics. Dahlhausen et al [46] report that individuals that underwent antibiotic therapy and subsequently died harboured gut microbial communities reduced in diversity and abundance of tannin-detoxifying bacteria essential to koala nutrition and survival. Finally, captive environments may reduce populations of beneficial host-associated microbes directly, with downstream effects on host health.…”
Section: (E) Captivitymentioning
confidence: 99%
“…In previous work, we identified L. koalarum as the most predictive taxon of koala survival during antibiotic treatment and we suggested that this bacterium is important for koala health ( Dahlhausen et al, 2018 ). Here, we isolated a L. koalarum strain from the feces of a healthy koala and sequenced and characterized its genome.…”
Section: Resultsmentioning
confidence: 92%
“…Tannins bind proteins followed by the formation of a precipitate, which cannot be digested by koalas or utilized by microbes ( Adamczyk et al, 2017 ). In our previous work, L. koalarum was identified as the most predictive taxon of koala survival during antibiotic treatment ( Dahlhausen et al, 2018 ). Briefly, a co-occurrence network analysis identified four bacterial taxa, including one of the genus Lonepinella , that could be found in feces of koalas that survived their antibiotic treatment after Chlamydia infection.…”
Section: Introductionmentioning
confidence: 99%